Essential norm estimates for Hankel operators on convex domains in C^2 - Čučković, Željko; Şahutoğlu, Sönmez (MATHEMATICA SCANDINAVICA, 2017)
Let Ω C^2 be a bounded convex domain with C^1-smooth boundary and φ C^1(Ω) such that φ is harmonic on the non-trivial disks in the boundary. We estimate the essential norm of the Hankel operator H_φ in terms of the derivatives of φ “along” the non-trivial disks in the boundary.